INDONESIAN EFL PRE-SERVICE TEACHERS CRITICAL THINKING PRACTICE IN ENGLISH INSTRUCTION - Fitriani, Sa'adatul; Agustina, Noni (JIPIS, 2023)
This study aims to examine the application of critical thinking conducted by Indonesian EFL pre-service teachers in English instruction. This study focused on four pre-service teacher participants and used a qualitative approach, narrative research design with observation and interviews as data collection instruments. This study addresses to Bloom Taxonomy critical thinking framework. The result the application of critical thinking applied by pre-service teachers is at a low to moderate level. Keywords: Critical thinking, pre-service teachers, Bloom Taxonomy